GUITAR QUINTET ОP. 143 BY MARIO CASTELNUOVO-TEDESCO THROUGH THE PRISM OF THE GENRE'S TRADITIONS - Halla, Illia (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2025)
The relevance of the study lies in the need for a more holistic understanding of the history of the development of genres that are common in the repertoire of modern guitarists. The main objective of the study is to study Mario Castelnuovo-Tedesco's "Quintet", Op. 143, through the prism of the traditions of the genre. The methodology is based on the application of the following methods: comparative (to identify common and divergent features between guitar quintets), structural-functional, genre, intonation-dramaturgical (for a holistic analysis of works), as well as the method of theoretical generalization (to summarize). The main results and conclusions. Thus, through the examination of Quintet op. 143 by Castelnuovo-Tedesco within the framework of genre analysis and by comparing it with the most prominent exemplars of the genre from previous centuries—such as the quintets of L. Bockernini, J. Schnabel, M. Giuliani, and E. Shand — it is possible to observe a consistent adherence to traditional formal conventions. For instance, the classical four-movement sonata cycle can be discerned in the works of L. Bockernini and J. Schnabel. However, it is noteworthy that with the advent of late Classicism and Romanticism, composers such as M. Giuliani and E. Shand either modified the number of movements within the sonata cycle or resorted to alternative cyclical forms. The role of the guitar in M. Castelnuovo-Tedesco’s Quintet op. 143 as the leading instrument —occasionally serving as the accompanying voice within the ensemble— remains consistent with traditional practices and is logically justified. The transformation of the guitar from an accompanying instrument to a principal solo instrument can be distinctly traced across all the works discussed in the article, especially when arranged in chronological order. Additionally, one may draw attention to the innovative and creative approaches in utilizing unconventional intonational material, as exemplified in the quintets by E. Shand and M. Castelnuovo-Tedesco. It is also pertinent to highlight Castelnuovo-Tedesco’s compositional mastery in the realm of guitar writing. Despite not being a professional guitarist himself, the composer succeeded in elevating the guitar to a soloistic role within the ensemble, comparable to that of professional guitarists and composers. Nevertheless, it should be acknowledged that the Italian-American artist also authored more virtuosic compositions for the instrument, reflecting a broad and sophisticated understanding of its technical and expressive capabilities.